KAJIAN KESEJAHTERAAN DI PROVINSI BENGKULU: SEBUAH TEMUAN DARI ANALISIS JALUR - Ratu Eva Febriani; Yusnida Yusnida (Universitas Bengkulu, 2020)
The paper conducts a quantitative appraisal of existing empirical testing on economic variable determinants of welfare in Bengkulu Province, analyze how economic growth dan income inequality affect welfare in Bengkulu Province directly or and using an intermediary variable. To capture this issue, path analysis is applied in this study as to the analysis method. The study addressed the measurement of the welfare of Bengkulu Province using the Human Development Index, and using the Williamson Index as representative of income inequality, also apply observational data for all variables in the period 2005-2017. The result shows that economic growth and income inequality to be associated with welfare in Bengkulu Province, and income inequality is proven an intervening variable affecting welfare. Keywords : Welfare1, Economic Growth2, dan Income Inequality 3